Crystal structures of two 1:2 dihydrate compounds of chloranilic acid with 2-carboxypyridine and 2-carboxyquinoline - Kazuma Gotoh (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The crystal structure of the 1:2 dihydrate compound of chloranilic acid (systematic name: 2,5-dichloro-3,6-dihydroxy-1,4-benzoquinone) with 2-carboxypyridine (another common name: picolinic acid; systematic name: pyridine-2-carboxylic acid), namely, 2C6H5.5NO20.5+·C6HCl2O4−·2H2O, (I), has been determined at 180 K, and the structure of the 1:2 dihydrate compound of chloranilic acid with 2-carboxyquinoline (another common name: quinaldic acid; systematic name: quinoline-2-carboxylic acid), namely, 2C10H7NO2·C6H2Cl2O4·2H2O, (II), has been redetermined at 200 K. This determination presents a higher precision crystal structure than the previously published structure [Marfo-Owusu & Thompson (2014). X-ray Struct. Anal. Online, 30, 55–56]. Compound (I) was analysed as a disordered structure over two states, viz. salt and co-crystal. The salt is bis(2-carboxypyridinium) chloranilate dihydrate, 2C6H6NO2+·C6Cl2O42−·2H2O, and the co-crystal is bis(pyridinium-2-carboxylate) chloranilic acid dihydrate, 2C6H5NO2·C6H2Cl2O4·2H2O, including zwitterionic 2-carboxypyridine. In both salt and co-crystal, the water molecule links the chloranilic acid and 2-carboxypyridine molecules through O—H...O and N—H...O hydrogen bonds. The 2-carboxypyridine molecules are connected into a head-to-head inversion dimer by a short O—H...O hydrogen bond, in which the H atom is disordered over two positions. Compound (II) is a 1:2 dihydrate co-crystal of chloranilic acid and zwitterionic 2-carboxyquinoline. The water molecule links the chloranilic acid and 2-carboxyquinoline molecules through O—H...O hydrogen bonds. The 2-carboxyquinoline molecules are connected into a head-to-tail inversion dimer by a pair of N—H...O hydrogen bonds.